Combination of Starch and Pectin as Raw Materials for Making Edible Film - Meldha, Zuqni; Fermi, Muhammad Iwan; Legawati, Lisa; Liska, Salma; Yolanda, Yogi; Hendri, Yola bertilsya; Amri, Idral (Journal of Engineering Science and Technology Management, 2026)
Food spoilage, driven by factors like microbes and oxygen, is a major challenge in food preservation. Edible films offer an eco-friendly and biodegradable solution, acting as a protective barrier that reduces waste and extends a product's shelf life. While starch is a common and affordable material for these films, it has limitations, including poor water resistance and brittleness. This study investigates combining starch and pectin to create a superior composite edible film. This approach leverages the synergistic interaction between the two materials, which forms a more stable, dense structure through hydrogen bonds. This combination enhances key properties like tensile strength, flexibility, and water vapor resistance. The specific structure of the pectin, such as its level of methylation, is crucial, as it directly impacts how well it blends with starch and the film's final performance. By carefully controlling these interactions, the resulting edible films can achieve properties comparable to some fossil-based plastics, positioning them as a promising and sustainable alternative for food packaging. To support these findings, this research will analyze and review key performance factors from studies published over the past five years.